Effectiveness of Digital Marketing Supporting SDGs in Indonesia: Study of the SMEs and Entrepreneurial Intention - Devi Setyowati; Riza Yonisa Kurniawan; Komm Pechinthorn (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: This research is a Systematic Literature Review (SLR) that analyzes the effectiveness of digital marketing in supporting SDGs in Indonesia, with a specific focus on the Small Medium Enterprise (SMEs) sector and the fundamental role of the entrepreneurial intentions of SMEs actors. Method: Through a rigorous process of searching, filtering, and evaluating scientific publications from leading databases, this study identifies, synthesizes, and interprets key findings regarding how the adoption and implementation of digital marketing by SMEs contribute to business performance and, in aggregate, to national economic growth. The role of the intent to strive as an important antecedent in the success of the digital adaptation of SMEs will also be explored in depth.  Results:  The results of this SLR are expected to provide a comprehensive overview of the existing research conditions, highlighting success factors and challenges, as well as identifying research gaps for future study agendas.Novelty: The implications of the policy for the government and other stakeholders are recommended to support Indonesian MSMEs in maximizing their digital marketing potential for the development of an inclusive and sustainable economy as a form of implementing the SDGs program.